Evaluation of lipid profile, high-sensitivity C-reactive protein and D-dimer in users of oral contraceptives of different types - João Victor M. Guedes; Natália R. Nunes; Letícia G. R. Ferreira; Thaís G. Vilar; Melina B. Pinheiro; Caroline P. Domingueti (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT Introduction: The use of oral contraceptives increases women's risk of developing cardiovascular and thromboembolic diseases, due to alterations in hemostatic and lipid profile. Objectives: Analyze the association between the use of different types of oral contraceptives with lipid profile and levels of serum high-sensitivity C-reactive protein (hsCRP) and plasma D-dimer. Methods: One hundred fifty-four participants were divided into the following groups: control nonusers (n = 41), medium-dose users (n= 32), third-generation low-dose users (n = 40), and fourth-generation low-dose users (n = 41). Triglycerides and total cholesterol serum levels were determined by colorimetric enzymatic method; high-density lipoprotein (HDL) cholesterol levels, by precipitation method; low-density lipoprotein (LDL) cholesterol levels, by Friedewald equation; hsCRP levels, by immunoturbidimetric method; and D-dimer levels, by fluorescence immunoassay. Results: Oral contraceptive users had higher serum levels of triglycerides, total cholesterol, HDL cholesterol (HDL-C), HDL/LDL index and hsCRP compared to controls. Medium-dose users had higher D-dimer plasma levels than controls and higher triglycerides serum levels than low-dose users. Triglycerides, hsCRP and D-dimer were positively correlated to each other. Conclusion: The use of combined oral contraceptives was associated with an unfavorable lipid profile and a chronic subclinical inflammation, with atherogenic potential. Furthermore, medium-dose contraceptives induced a higher thrombogenic potential, since they were associated with increased D-dimer levels in comparison to low-dose ones.